Comparison of Effects Beclomethasone Dipropionate with Flunisolide in Patients with Allergic Rhinitis - Maryiam Asghar; Muhammad Tayyab Rasheed; Amir Akbar; Farhat Jabeen Malik; Deepak Rai; Liaquat Ali (Life and Science)
Objective: To compare the effectiveness of beclomethasone dipropionate with flunisolide given twice daily in terms of improvement in symptom score after 14 days of treatment in allergic rhinitis patients. Study Design: Quasi-Experimental Study. Place and Duration of Study: The study was carried out at the Department of ENT, PAF Hospital E-9 Islamabad, Pakistan, from January 2021 to July 2021. Materials and Methods: All patients of age 20-60 years of either gender having allergic rhinitis were included in the study. Allergic rhinitis was defined as any patient with a history of running nose with seasonal changes or exposure to allergens diagnosed by a consultant ENT surgeon. Patients with a history of smoking, asthma, having deviated nasal septum and inferior turbinate hypertrophy, patients already treated with Beclomethasone dipropionate or flunisolide, patients having an acute upper respiratory infection, and pregnant females were excluded from the study. A consecutive sampling technique was applied for the selection of participants. Patients were randomly divided into two groups: Group-A was given beclomethasone dipropionate, and Group-B Group-B was given flunisolide. The daily dose during treatment was 0.1 mg of beclomethasone dipropionate (50 ugs per puff) two-time each medicine daily. And dose of flunisolide nasal solution (flunisolide nasal spray 0.025%) flunisolide 50 micrograms in each nostril twice daily were 2 sprays (50 ugs) in each nostril 2 times a day: Treatment was continued for two weeks in each group. The symptoms score was estimated at baseline and after two weeks of intervention. Data were analyzed with the help of SPSS version 20. Results: The mean age of the study participants was 41.17+8.58 years in beclomethasone dipropionate and 41.85+8.52 years in flunisolide. Efficacy of flunisolide was significantly higher in terms of improvement in symptom score after 14 days of treatment in patients of allergic rhinitis compared to beclomethasone dipropionate (85% vs 79.58, p=0.035). Conclusion: Flunisolide inhaler is more effective when compared with beclomethasone dipropionate for treating allergic rhinitis.